LEARNING PROFILES OF SOCIAL WORK STUDENTS: WHO ARE YOU AND HOW SHOULD THIS INFLUENCE MY TEACHING? - Dykes, Glynnis; Green, Sulina (Social Work/Maatskaplike Werk, 2016)
This qualitative study explores the impact of adverse childhood experiences (ACEs) of social work students on notions of students’ learning profile. Data were obtained from both student and staff participants on third year level within the social work programme during the teaching of a particular module focusing on family wellbeing. The implications of strong reactions during teaching and learning are juxtaposed against the notions of students’ learning profile and participants’ teaching and learning suggestions. Several recommendations are made that have emerged from the study that attempt to relate to students’ learning profile in social work professional learning.